2019
DOI: 10.1001/jamadermatol.2018.5221
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Antibiotic Treatment of Acne With Skin Microbiota Characteristics

Abstract: IMPORTANCE Given the widespread use of systemic antibiotics for treatment of moderate to severe acne, it is important to understand the associations of such antibiotic use with changes not only in Cutibacterium acnes (formerly Propionibacterium acnes) but also in the complete bacterial community of the skin. OBJECTIVE To examine the composition, diversity, and resilience of skin microbiota associated with systemic antibiotic perturbation in individuals with acne. DESIGN, SETTING, AND PARTICIPANTS This long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 54 publications
3
82
1
Order By: Relevance
“…Whether or not the relative abundance of C acnes is greater in acne patients compared to healthy controls, or whether the levels correlate with disease severity, is unclear. Nonetheless, all studies to date support C acnes as a factor in acne pathogenesis . A small pilot study with 8 pre‐adolescent acne patients demonstrated that in addition to C acnes , both Streptococcus and Staphylococcus spp.…”
Section: Acnementioning
confidence: 99%
See 3 more Smart Citations
“…Whether or not the relative abundance of C acnes is greater in acne patients compared to healthy controls, or whether the levels correlate with disease severity, is unclear. Nonetheless, all studies to date support C acnes as a factor in acne pathogenesis . A small pilot study with 8 pre‐adolescent acne patients demonstrated that in addition to C acnes , both Streptococcus and Staphylococcus spp.…”
Section: Acnementioning
confidence: 99%
“…Few studies demonstrate the direct effects of acne treatments on the skin microbiome. In general, benzoyl peroxide, lymecycline, topical clindamycin, isotretinoin, and oral minocycline all decrease the bacterial load on the skin, including C acnes , and increase bacterial diversity on the skin by the end of treatment . These treatments are not specific to C acnes , but instead trigger global diversity changes within the skin microbiome community, changes that may persist well beyond the treatment end date.…”
Section: Acnementioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies for the manipulation of the skin microbiota have been suggested, including hygiene products [11], antibiotics [12,13], and prebiotics [14]. These methods, however, often suffer from poor e cacy and lack of selectivity towards the pathogenic bacteria [15].…”
Section: Introductionmentioning
confidence: 99%